STUDY OF STORAGE AND RETRIEVAL OF SINGLE-PHOTON QUANTUM STATE IN A COLLECTIVE ATOMIC EXCITATIONS - BABAYO, I.I.; LIMAN, A.M; AHMED, A.B (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
In this article, the probe pulse (that is, of single-photon quantum states) which can be stored in long live cavity dark state is investigated. The transfer of the single photon state to the collective cavity dark state can be accomplished with nearly a hundred percent efficiently by the method of intracavity EIT and assumption of quantum impedance matching condition whereby the classical driving field is adiabatically switched off while the probe laser is inside the dense ensemble of atoms and cos θ is optimized for any input pulse respectively is clearly described. It is noted that, this method of using an optically-dense many-atom medium is far superior and efficient than the technique with single atoms processed in the strong coupling system.